Novel method for enhancing permeate flux of submerged membrane system in two-phase anaerobic reactor - Lee, SM; Jung, JY; Chung, YC (PERGAMON-ELSEVIER SCIENCE LTD, 2001)
A two-phase anaerobic reactor system with a submerged membrane in the acidogenic reactor was designed for the enhancement of organic acid conversion and methane recovery. A submerged membrane system in a two-phase anaerobic reactor was tested to increase the sludge retention time (SRT) of acidogen and to enhance the solid separation. The pilot plant experiment was performed for piggery wastewater treatment for a year. The membrane material used was mixed esters of cellulose of 0.5 mum pore size. COD removal efficiency was 80% and the methane production showed 0.32 m(3)/kg COD removed for the submerged membrane system in the anaerobic digester. As the cake resistance of the membrane caused a serious problem, a stainless-steel prefilter and air backwashing methods were applied to minimize the cake resistance effectively. Among the tested prefilters, the 63 mum pore prefilter showed the best performance for reducing cake resistance and a successful long-term operation. By cleaning with alkali first and acidic solutions later, the permeate flux decreased by long-term operation was recovered to 89% of that with a new membrane. (C) 2000 Elsevier Science Ltd. All rights reserved
Keywords: PERFORMANCE; DIGESTION